Femoral parallelism: evaluation and impact of variation on canine hip dysplasia assessment - Franco-Gonçalo, Pedro; Alves-Pimenta, Sofia; Gonçalves, Lio; Colaço, Bruno; Leite, Pedro; Ribeiro, Alexandrine; Ferreira, Manuel; McEvoy, Fintan; Ginja, Mário (Frontiers in Veterinary Science, 2023)
Adequate radiographic positioning on the X-ray table is paramount for canine hip dysplasia (HD) screening. The aims of this study were to evaluate femoral parallelism on normal ventrodorsal hip extended (VDHE) view and the effect of femoral angulation (FA) on Norberg Angle (NA) and Hip Congruency Index (HCI). The femoral parallelism was evaluated comparing the alignment of the long femoral axis with the long body axis in normal VDHE views and the effect of FA on NA and HCI on repeated VDHE views with different levels of FA. The femoral long axis in normal VDHE views showed a ranged of FA from -4.85° to 5.85°, mean ± standard deviation (SD) of -0.06 ± 2.41°, 95% CI [-4.88, 4.76°]. In the paired views, the mean ± SD femur adduction of 3.69 ± 1.96° led to a statistically significant decrease NA, and HCI, and femur abduction of 2.89 ± 2.12 led to a statistically significant increase in NA and HCI (p < 0.05). The FA differences were also significantly correlated with both NA differences (r = 0.83) and HCI differences (r = 0.44) (p < 0.001). This work describes a methodology that allows evaluation of femoral parallelism in VDHE views and the results suggest that femur abduction yielded more desirable NA and HCI values and adduction impaired NA and HCI values. The positive linear association of FA with NA and HCI allows the use of regression equations to create corrections, to reduce the influence of poor femoral parallelism in the HD scoring.